A New Location for a Rare Legume Flemingia rollae (Family Fabaceae) and Notes on its Typification - Gavade, Sandip K.; Nandikar, Mayur D.; Shimpale, Vinod B.; Lekhak, Manoj M. (Journal of the Bombay Natural History Society (JBNHS), 2016)
No Abstract.